Kandungan Glutathione pada sayur asparagus (Asparagus officinalis L.) untuk perawatan kulit - Yahya, Azzahra Aulia (Maliki Interdisciplinary Journal, 2024)
Asparagus plants are plants that have rich nutrients and have various benefits that are good for the human body. Asparagus plants are included in the Liliaceae family of plants, so they can live for years. Asparagus plants are also classified as horticulture which has high economic value in global and national and international reach. The glutathione content has a function as brightening the white pigment by reducing the melanin pigment which causes the skin color to become darker. The content of glutathione can relieve acne, improve skin texture, and of course reduce the symptoms of aging on the skin. The process of glutathione content in brightening the skin is by inhibiting tyrosinase activity, reducing pigment. The content contained in asparagus plants includes vitamins C, E, B6, A, K, calcium, magnesium, zinc, protein and so on. There is fiber in asparagus which will launch the digestive organ system. The weak fat contained in asparagus plants includes 0.12 grams of saturated fat, 0.02 grams of single fat, 0.23 grams of double fat. The research in this paper uses quantitative methods. It describes the processing of asparagus into capsules containing glutathione. The process involves selecting fresh asparagus, cleaning, oven drying, grinding to a fine powder, and sieving to produce a powder which is then put into number 4 sized capsules.